The mind electric : a neurologist on the strangeness and wonder of our brains - Anand, Pria (Washington Square Press/Atria Books, an imprint of Simon & Schuster, LLC, 2025)
"A feminist view of the intimate stranger that is the brain, and an overdue reckoning with the misogyny and racism within neuroscience"--